2005
DOI: 10.1597/04-142r.1
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Supply to the Soft Palate Muscles with Special Reference to the Distribution of the Lesser Palatine Nerve

Abstract: The soft palate is considered to be located in the border region between the areas of distribution of the lesser palatine nerve and pharyngeal plexus. This may be why controversies exist in previous studies about the innervation of the soft palate muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 11 publications
3
39
0
1
Order By: Relevance
“…12 The activation of these nerves is required to prevent upper airway collapse. In addition, there were significantly fewer peripheral nerve branches innervating the palatine muscles of the dogs with an elongated soft palate, compared with findings in the control dogs.…”
Section: Discussionmentioning
confidence: 99%
“…12 The activation of these nerves is required to prevent upper airway collapse. In addition, there were significantly fewer peripheral nerve branches innervating the palatine muscles of the dogs with an elongated soft palate, compared with findings in the control dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies that do not support the LVP as being innervated by the facial nerve in experimental animals such as Macacus sinicus (Beevor and Horsley, ), dog (Rich, ), or cat (van Loveren et al, ; Keller et al, ), Sonobe () demonstrated with both electrophysiological experiments and morphological investigations using rats that the LVP is innervated by the facial, glossopharyngeal, and vagus nerves. There is an acceptable explanation for the failure of other studies to find and identify the component of the facial nerve in the LVP (Shimokawa et al, ). Specifically, the pharyngeal plexus innervates most of the superior part (near the origin) of the LVP, and the LPN innervates a very small inferior part of the LVP (near the insertion); that is, the component of the facial nerve is often too small to find and identify.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The lesser palatine nerve distribution represents the majority of the resected anatomy in a UPPP procedure; therefore, this nerve seems to be an ideal target for postoperative continuous regional analgesia. This nerve descends through the pterygopalatine canal and emerges from the lesser palatine foramen in the palatine bone, where it is accessible surgically or transmucosally using anatomic landmarks.…”
Section: Discussionmentioning
confidence: 99%